Urban Space Governance and Sustainable Green Development in Indonesia - Adiyanta, F. C. Susila (International Journal of Energy Economics and Policy, 2019)
The development of urban areas and settlements by the government and the private sector has an impact on the environment, for that they need to develop a city planning plan based on the concept of environmentally friendly sustainable development. The main issues of this study are the background, parameters, and urgency of urban planning development based on the concept of sustainable development that is environmentally friendly. This study uses a sociolegal approach, and aims to describe, and explain various factors that are taken into consideration for the establishment of a city planning plan policy based on the concept of environmentally friendly sustainable development. The results of the study: a) geographical, topographic conditions, social, economic and environmental issues are the basis for consideration of urban planning development based on the concept of environmentally friendly sustainable development; b) the principles of democracy, justice and sustainability are parameters of urban planning development based on the concept of environmentally friendly sustainable development; and c) the urgency of urban planning based on the concept of environmentally friendly sustainable development is the realization of public welfare. The recommendations of this study are: a) planning of development activities and development of residential areas must fulfill licensing requirements, analyze environmental impacts and aspirations of the community; b) there is a need to strengthen the capacity of supervisory institutions that involve the public in all activities for implementing development policies and developing residential areas. Keywords: regulation, urban space governance, sustainable environment-based development JEL Classifications: O18, Q01 DOI: https://doi.org/10.32479/ijeep.8065